Some Inevitable Remarks on “Tripled Fixed Point Theorems for Mixed Monotone Kannan Type Contractive Mappings” - Hamed H. Alsulami; Antonio-Francisco Roldán-López-de-Hierro; Erdal Karapınar; Stojan Radenović (Journal of Applied Mathematics)
We advise that the proof of Theorem 12 given by Borcut et al. (2014) is not correct, and it cannot be corrected using the same technique. Furthermore, we present some similar results as an approximation to the opened question if that statement is valid.